Estádio Olímpico Monumental: o templo da imortalidade - Silva, João Batista Lopes da (2018)
This research constitutes a rescue of the sense of memory of the Monumental Olympic Stadium, located in Porto Alegre, Rio Grande do Sul, Brazil, which was the official stadium of the Foot-Ball Porto Alegre Alegrense from 1954 to 2013. In that last year, has begun a demolition process that is under way. As it is a sport plaza with a great cultural repercussion, as well as a football heritage and has an identity bond of Grêmio supporters, this research is justified. The general aim was to understand, analyze and seek for the meaning of the Monumental Olympic Stadium as a "place of memory" - a concept developed by the French historian Piere Nora - from the voices of social actors who have a bond of belonging to the Grêmio Foot-Ball Porto Alegrense and the stadium itself. For the specific aims we seek to contribute to the registration of collective memory by analyzing the impacts that the demolition of the Monumental Olympic Stadium can cause, already causes / caused in the people who make or were part of the history of the stadium, especially to those who are, in some way, involved in the design and dismemberment of major football events. The theoretical contribution, beyond Pierre Nora, are based on research authors that corroborate the studies of memory and identity such as Maurice Halbwachs, Joël Candau, Michel Pollak, Ecléa Bosi, Zygmunt Bauman; and authors who discuss the memories of the Monumental Olympic Stadium from characters who made history in that place, such as Léo Gerchmann and Eduardo Bueno. The research has a qualitative ethnographic basis, using oral history techniques, since it is characterized by the search for the understanding of the meanings narrated by the twenty-two interviewees about a cultural heritage conceived in a particular and emotional way in the imaginary of these social actors and it uses the description and interpretation of data in a natural context in which the place of memory is characterized as being a cultural component presented in the life and social experiences of the group involved. In addition to the in-depth interviews, that stimulated the narratives of the social actors and, therefore, is the main instrument of data collection, we use as empirical sources a field journal of the researcher, journalistic materials and official documents of the club. For the process of analysis, we list seven categories of analysis, chosen a posteriori. They are: "The Olympic Stadium as patrimony"; "Memory and identity: the notion of belonging"; "The monumental games at the Olympic Stadium"; "The personification of the place"; "The stadium as a place of memory"; "Diversity and gender in the field and in the stands" and "From collective catharsis to the drama of demolition". At the end of the study, we can consider that people who have a relation of belonging to the Olympic Stadium, at the same time, they suffer from the loss of a physical structure that refers to a place of memory with great significance for the construction of their identity and also affective bonds, they elevate the Monumental Olympic Stadium to a dimension that transcends matter, personifies the place and strengthens the characterization of a place of memory that has aura.